1996
DOI: 10.1007/bf02318970
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration from somatic embryos in black pepper

Abstract: Embryogenic callus derived from zygotic embryos of black pepper (Piper nigrum Linn.) were induced to form somatic embryos on solid and liquid Schenk and Hildebrandt basal medium. Callus proliferation, somatic embryogenesis and germination of embryos were achieved in about 8 months in static cultures while it took only 8 weeks in liquid suspension cultures. The highest number of embryos and plantlets was produced from cells grown as suspension cultures raised in half-strength medium without growth regulators an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
1
9
1
3
Order By: Relevance
“…Suspension cultures induced the highest number of somatic embryos. Similar results have been reported in black pepper (Joseph et al, 1996) and Holostemma ada-kodien (Martin, 2003), where high-frequency embryo formation occurred in suspension cultures compared to a lower frequency in static cultures. In the present study a 100 mg callus induced more than 500 somatic embryos (5000 embryos per g callus) ( Table 2).…”
Section: Resultssupporting
confidence: 88%
“…Suspension cultures induced the highest number of somatic embryos. Similar results have been reported in black pepper (Joseph et al, 1996) and Holostemma ada-kodien (Martin, 2003), where high-frequency embryo formation occurred in suspension cultures compared to a lower frequency in static cultures. In the present study a 100 mg callus induced more than 500 somatic embryos (5000 embryos per g callus) ( Table 2).…”
Section: Resultssupporting
confidence: 88%
“…To date, there have been no reports on the successful in vitro regeneration of P. nigrum from leaf explants of potted plants. However, several protocols for regeneration and somatic embryogenesis in P. nigrum from shoot tips and nodal explants have been published (Philip et al 1992;Bhat et al 1995;Joseph et al 1996;Nair and Gupta 2006). Kapoor et al (2009) recently demonstrated that the protective effect of piperine is most likely due to its antioxidant activity.…”
Section: Gibberellic Acid á Organogenesis á Piper Nigrummentioning
confidence: 99%
“…MS medium without plant growth regulators NAA a-Naphthaleneacetic acid PGRs Plant growth regulators Piper nigrum L. (black pepper) is a flowering vine in the family Piperaceae that is primarily cultivated for its fruit, which is usually dried and used as a spice and seasoning (Joseph et al 1996). Black pepper is native to South India and is extensively cultivated there and elsewhere throughout the tropical regions.…”
Section: Gibberellic Acid á Organogenesis á Piper Nigrummentioning
confidence: 99%
“…Karimunda, Panniyur-1; hoAEc tõ nu«i cÊy m« sÑo cña Piper longum L. [1,4,5,7] nh−ng ch−a cã c«ng tr×nh nghiªn cøu ë ViÖt Nam vÒ nh©n gièng c©y hå tiªu s¹ch virut.…”
Section: Viön Khoa Häc Kü Thuët N«ng Nghiöp Miòn Namunclassified